Building Influencer Popularity Trends Through Beauty Content on Tiktok - Azzahra, Putri Salsabilla; Alianza, Ika; Imawan, Khaerudin (Journal Research of Social Science, Economics, and Management, 2025)
. TikTok is an effective platform for influencers to build popularity and increase interaction with audiences. This study aims to analyze Tasya Farasya's strategy in conveying beauty content on TikTok and its contribution to engagement and popularity. Using descriptive qualitative methods, data were collected through documentation, observation, and interviews. Data analysis was carried out using a qualitative content analysis approach. New media theory (Flew, Power, and Littlejohn) is used to understand the role of TikTok's digital interactivity, while Social Influence Theory (Kelman) explains Tasya's influence through three levels: compliance, identification, and internalization. The results of the study showed that Tasya Farasya leveraged TikTok's interactive features, such as comment replies, viral trends, and direct interactions to build engagement. The storytelling technique in product reviews and the "Tasya Farasya Approved" label also strengthens her credibility as a beauty influencer. The study concludes that influencer success depends not only on the quality of the content, but also on communication strategies, audience engagement, and the ability to build trends and trust. These findings are expected to be a reference for influencers and content creators in developing effective strategies on social media, especially TikTok.